The evaluating tools of the evidence in the administrative process - Stoian, Anna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
Problem statement. Ukraine’s desire to meet the standards of a democratic state has become the leitmotif of numerous changes in the legal field of the state, especially in the field of administrative justice. The constant improvement of evidence as one of the central institutions of every procedural branch of law is the key to the harmonious development of the entire judicial system. This article is devoted to the study of the last stage of proof - the evaluation of evidence, which has become relevant in connection with the involvement of foreign evaluating tools in the form of standards of proof. This trend, on the one hand, has increased the field of potential scientific research and, on the other, created gaps and incomplete knowledge at both theoretical and praxeological levels regarding the concept, place and features of the standards of proof. The purpose of the article is to update the fundamental knowledge about the judge’s evaluating ways of the evidence in the administrative process and to provide a sectoral definition of standards of proof, and also evaluating tools and the kinds of tools. Methods. With the help of comparative-legal and formal-legal methods the essence of the concept of proving both general and branch concept, and also an estimation of proofs as a final stage of proving in administrative process is investigated. Incidentally, the formal-legal method became the basis for creating a definition of standards of proof and tools for evaluating evidence in the administrative process. The historical-legal method allowed us to trace the genesis of ways to objectify the internal and external side of the evaluation of evidence. The use of hypothesis, assumption, and modeling techniques has helped to create proposals for enshrining the standard of proof in the Code of Administrative Procedure as an additional tool to objectify the mental aspect of a judge’s evaluation of evidence. Results. It is established that among scientists there are no significant differences in understanding both the concept of proof and administrative-procedural proofing. The decision’s ability to correspond the criteria of fairness, legality and reasonableness depends on the proper evaluation activities of the judge. It was established that the evaluation of evidence includes two components: logical and normative, which have different ways of objectification. The ways how to objectificate the logical aspects of evaluating evidence were indicated. Such kind of activities should involved constant improving of the legal norms , increasing the requirements for potential judges and synchronously applying the concept of inner conviction and the standards of proof. Besides that the standards of proof should be allocated as additional instrument of objectification the psychological process of the judge’s evaluating activity in administrative process. The ways of describing the definition of standard of proof were also analyzed. The definition of the standard of proof in administrative process were proposed. The propositions of changes and additions to the Code of Administrative Procedure of Ukraine have been formed. Conclusions. The evidence’s evaluation is being not influenced by features of the administrative process. The difference between the evaluation of evidence in different processes is the presence or non-existing of a legally established standard at the level of the relevant law. The party’s ability to evaluate evidence in the proper way is the key for realization reasonable procedural deadlines. The judge’s evaluation of the evidence has a greater impact on the intermediate or final decision, than another one else. The structure of the evidence’s evaluation include inner and outer sides. Every of this sides are being different ability to be understood by other people. The inner part are being contained less objectification’s ability, but scientists continue to develop useful ways in order to control the process of accepting the decision and here some of them: 1) creating high requirements for the potential judge during the selection of professional corps of judges; 2) improving the judicial norms; 3) implementation of the standards of proof as an additional tool of evidence’s evaluation, which assist to create internal conviction.